Water Rights: A key to sustainable development in Nepal - Shrestha, Madhav Narayan (Journal of Hydrology and Meteorology, 2011)
By addressing water, one will also address human development. People’s lack of access to safe and secure water is not due to the quantity of water available on the earth but rather because the institutions set up to manage the issues are not up to the challenge. In Nepal Muluki Ain (Laws of Land) did not regulate water much in detail because water was not considered an important resource and a source of major revenue. Water rights are based on practices legitimized by law and they are related to political, economic and social relationship and to other rights such as land rights Muluki Ain (1854, 1952 and 1963),which regulates priority in acquiring water from water sources, and allocation of water. Acts promulgated between 1961 and 1992 reflect the growing importance of water resources in Nepalese political economy and not only empower the state to regulate water use, they also vested ownership of all water resources with the state. Although various Acts gave water rights to every citizen of Nepal, there are gender bias in executing power and rights to use water sources. Water scarcity problem can perhaps be due to geographical reality, climate change or to the excessive use of water resource in one sector and a resulting loss of raw water available for other uses. Issues such as good water governance, negotiation and collaboration for water sharing, awareness on values of water, management of water induced disasters etc needs specific attention. Keywords: muluki Ain (laws of land); Bhupati (land lords) DOI: http://dx.doi.org/10.3126/jhm.v6i1.5486 Journal of Hydrology and Meteorology, Vol. 6, No. 1 37-43